Detection of invasion gene invA in Salmonella spp. Isolated from slaughtered cattle by PCR method: Arcan A N Al-Zubaidy 1, Afaf Abdulrahman Yousif 2, Mawlood A. A. Al-Graibawi 3, Jalil Darkhan 4 - Al-Graibawi, Mawlood A. A. (The Iraqi Journal of Veterinary Medicine, 2015)
The present study was carried out for the identification and molecular characterization of Salmonella spp. isolated from cattle at abattoir by biochemical, serotyping and virulence gene based polymerase chain reaction (PCR) techniques. Eleven Salmonella were isolated from cattle at abattoir, these isolates were cultured and biochemically characterized by double checking with a conventional method and by KB011 Hi Salmonella TM identification kit then confirmed by serotyping and testing for detection of the invA virulence gene by PCR by using a Salmonella-specific 506 bp invA gene amplicon. The biochemical and serotyping results revealed that the 11 isolates belonged to four serotypes, S. enteritidis was the predominant serotype,5 isolates (45.45%) followed by S. newport 3 (27.27%), S. ohio, 2 (18.18%) and S. anatum, 1(9.09%). The PCR technique confirmed that all Salmonella isolates carried the invA gene (DNA amplification showed one distinct band with molecular weight of 506 bp amplified fragment on electrophoresis in agarose gel).The PCR assay described herein was found to be a rapid and simple method to confirm the isolates as Salmonella.